Teaching Creativity - Kurbanovna , Abdieva Dilfuza (Miasto Przyszłości, 2024)
Present time a lot of things are being created thanks to IT technology and accumulation of ideas involves learners to create something new in all spheres of life. Creating generates our system of ideas, supports logical views of something, imaginative overview towards the environment where we live and work. Creativity appears after creative-thinking. Furthermore, artificial intelligence makes our life better to live, provides us more opportunity than before, presenting enormous new technology to utilize in our workplaces. This paper highlights ideas regarding to creativity, artificial intelligence and its impact on society.